PECULIARITIES OF TOMATO GROWING TECHNOLOGY IN TRANSITION TURNOVER IN THE CONDITIONS OF PROTECTED GROUND OF DAGESTAN - P. M. Akhmedova (Овощи России)
The purpose of the research was to study and optimize the timing of growing tomatoes in conditions of transitional turnover, taking into account the natural and climatic conditions of Dagestan, biological features of culture, lighting conditions, market demand for vegetable products, profitability of production. Experimental studies were carried out in 2015-2016 in the greenhouse farm "Niva". The technology of tomato cultivation in winter and film greenhouses in the transitional turnover of the 6th and 7th light zone of the country is shown, its economic efficiency is shown in the light conditions of Dagestan. The studied F1 hybrids were distinguished by a good harvest yield from December to April, the highest yields were scored by hybrids: Tomimaru Mucho F1, Pink Paradise F1, providing 15.68 and 14.98 kg. The economic evaluation of the studied hybrids and varieties of tomato showed that during planting sowing and planting cannot be delayed, since plants fall into conditions of limited illumination by young ones that have not yet entered the phase of mass fruiting, and the harvest in the winter months is sharply reduced, profitability decreases. According to the average market price for the sale of tomato fruits in the winter months of 200 and 210 rubles per kg, depending on the timing of harvesting and marketing, the profitability of production of hybrids was in %%: Tomimaru Mucho F1 – 120-170, Tiwai F1 – 125-170, Pink Paradise F1 – 123-174, Revermun F1 – 90-110, Lvovich F1 – 123-159. Such profitability of cultivation of the studied varieties indicates that their growing in the transitional turnover is economically profitable.